Strategies to Inelasticize the Halal Food Industry in Indonesia - Bawono, Anton; Waluyo, Agus; Widiyanto, Asfa (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2024)
This research has three main objectives. First, to analyze the potential and prospects of the halal food industry in Indonesia. Second, analyze the elasticity of the halal food industry in Indonesia. Finally, formulate a strategy to inelasticize the halal food industry in Indonesia. The research approach used in this study is mixed methods, which combines quantitative and qualitative research. There are several important findings in this study. First, the potential and projection of the halal food industry in Indonesia, which is based on estimates for 2021, continues to grow. Second, the factors that influence the demand for halal food in Indonesia are income, price, advertising, and halal labeling, and the highest -lowest short-term elasticity values are price elasticity, halal labeling, advertising, and income. Finally, the strategy to inelasticize the halal food industry in Indonesia is divided into two, namely priority strategies and supporting strategies. Priority strategies include: Maintain the stability of people's income; Increase production efficiency (technical efficiency and price efficiency); Improve the quality of Human Resources (HR) and technology improvement; Application of tax incentives; Improving the quality and quantity of advertising; Socialization of halal labeling; Halal certification management; Development of halal supply; Development of halal logistics. Supporting strategies consisting of Need for innovation in the development of halal food industry products; Guarantee of legal certainty and quality of halal food products; Increased ease of location and access; Service innovation; Improved facilities.